Analisis Perbandingan Produksi dan Pendapatan Petani Kopi dengan Benih Bersertifikat dan Tidak Bersertifikat di Kecamatan Siborongborong - Sugiono, Nurhabsah Anggraini; Rahmanta, Rahmanta; Sibuea, Muhammad Buhari; Kuswardani, Retna A. (Universitas Medan Area, 2021)
Coffee farming has an important role in increasing foreign exchange, expanding employment and increasing farmers' income. Coffee production has not been able to increase, partly because not many farmers have used quality seeds, namely certified seeds. This study aims to determine the differences in production and income of farmers using certified seeds and farmers using uncertified seeds. The research was conducted in Siborongborong District, North Tapanuli Regency, North Sumatra Province, as a center for coffee plantations, from February to March 2020 with 60 farmer respondents, consisting of 30 farmers using certified seeds and 30 who did not. The results showed that coffee production using certified seeds was greater than coffee production using uncertified seeds or significantly different, with a difference of 380.77 kg per hectare. The income of coffee farmers using certified seeds is greater than that of coffee farmers using uncertified seeds, with a difference of Rp. 5,611,997 per hectare. There is a significant difference between the income of coffee farmers who use certified seeds and the income of coffee farmers who use uncertified seeds, where the income of coffee farmers with certified seeds is greater. The calculation results show an increase in production of 1.8 times and an increase in income of 3 times with the use of certified seeds.